THE ROLE OF TELEVISION ON THE BEHAVIOUR AND HEALTH OF CHILDERN - M. Bajoghli; M. Beheshti (Tehran University of Medical Sciences, 1977)
Television is being seen and heard increasingly in many homes. Its effects on health of youth and pollution of the mind are of considerable interest, research and concern. The review of the two most popular daily newspapers of Iran revealed alarming examples of violence in children imitating the aggressive acts of the television scene. Since children are more vulnerable than adults, parents should be informed and guided about impact of watching television on their children.